Kisspeptin improves local ovarian insulin resistance in PCOS by modulating the PI3K/AKT/GLUT4 signaling pathway - Na Sun; Pingping Sun; Lilan Sun; Ping Sun; Dandan Qi; Huagang Ma (PLoS ONE, 2026)
Background Insulin resistance (IR) is commonly observed in patients with polycystic ovary syndrome (PCOS), affecting 44% to 70% of these individuals. Kisspeptin is a key regulatory factor in energy balance and reproduction, and it may alleviate PCOS-related symptoms by improving insulin resistance. Methods In this study, a PCOS-IR mouse model was established using dehydroepiandrosterone (DHEA) and a high-fat diet. The expression of kisspeptin, PI3K, phosphorylated PI3K (p-PI3K), AKT, phosphorylated AKT (p-AKT), and glucose transporter 4 (GLUT4) was measured by immunofluorescence staining, quantitative PCR, and Western blotting. Flow cytometry was used to evaluate mitochondrial membrane potential (MMP) and reactive oxygen species (ROS) levels. Results In granulosa cells from PCOS-IR mice, kisspeptin upregulated GLUT4 expression by activating the PI3K/AKT signaling pathway. In vitro experiments showed that kisspeptin significantly reduced ROS levels, enhanced MMP, and improved mitochondrial function. Conclusion Kisspeptin improves insulin resistance through the PI3K/AKT/GLUT4 signaling pathway and exerts its effects in vitro in granulosa cells. by protecting mitochondrial function. This study provides potential biomarkers and therapeutic targets for the treatment of PCOS-IR.